Early Interactions of Rust Pathogen Puccinia arachidis (Speg.) with Groundnut Genotypes Varying in Resistance - Ramya, V.; Thilak, S. A.; Devi, G. Uma; S. N. C. V. L., Pushpavalli; Sudini, Hari K. (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted in the Department of Plant Pathology, College of Agriculture, Rajendranagar, Professor Jayashankar Telangana State Agricultural University, Hyderabad, India to understand the histopathological mechanisms of initial interaction of Puccinia arachidis with six groundnut genotypes. Fully expanded quadrifoliate leaves were inoculated with P. arachidis using the detached leaf assay. Five-mm leaf discs were cut at 6 hours after inoculation (hai) and each day until 5 days after inoculation (dai) and examined for histopathological interactions. Germination of urediniospores was detected during 6–8 hai and continued until 24 hai. There were no differences in pre-penetration and penetration among all the six genotypes. Differences in post-penetration were observed among the genotypes during 3–5 dai. In genotypes TMV 2 and K 6, extensive hyphal colonization was observed in the intercellular spaces of mesophyll cells by 4–5 dai indicating compatible interaction and susceptibility to rust disease. Sparse hyphal growth and corresponding mesophyll cell death at 3–5 dai in genotypes ICGV 171015 and ICGV 13229 indicated defense response by the host and moderate resistance. In genotypes ICG 11426 and GPBD 4, complete arrest of hyphal growth by 4–5 dai due to extensive mesophyll necrosis suggested incompatible interaction and resistance to rust. This is the first documentation of the histopathological description of the initial infection strategies of P. arachidis in the selected groundnut genotypes.